PENGARUH KEPERCAYAAN DIRI TERHADAP PERILAKU KONSUMTIF PADA SISWA KELAS XI SMA NEGERI 1 BABELAN - ASTI ASRI (Journal of Research and Measurement in Psychology, 2017)
Abstract This research is to know influence of self-confidence to consumptive behavior of 11th Students Senior High School 1 Babelan. The method used in this research is quantitative research methods using ex post facto design. The sampling technique in this study is a probability sampling with kind of purposive sampling. The amount of the samples is 82 respondents. The technique of the analysis data used to test the hypothesis is by simple regression test using SPSS version 16.00. Based on the counting result, mark F is 7.443 with mark of significance of 0.008. The regression similarity of Y = 83.413+ 0.246 X and the influence (adjusted R Square) of the variable self-confidence to consumptive behavior is 0.074 (7.4%), which means that the self-confidence affects the consumptive behavior to the number of 7.4% and the rest 92.6%, is affected by another factors. Therefore, Ho is rejected and Ha is accepted so that it can be concluded that there is a significant influence of selfconfidence to the consumptive behavior of 11th Students Senior High School 1 Babelan. Keyword: Self-Confidence, Consumptive Behavior